Selective Policy in Immigration to Facing Global Pandemic COVID-19 - Guntur Widyanto; Riri Ardyaningtyas (Polteknik Imigrasi, 2020)
Facing COVID-19 which is announced as pandemic global by World Health Organization (WHO), Indonesia government has established some policies to pretend COVID-19 spread in Indonesia territory. Directorate General of Immigration as authorized institution in immigration also established the policies, mainly for foreigner who stay in Indonesia territory.